2017
DOI: 10.1097/gox.0000000000001355
|View full text |Cite
|
Sign up to set email alerts
|

Versatility of the Latissimus Dorsi Free Flap during the Treatment of Complex Postcraniotomy Surgical Site Infections

Abstract: Background:Some intractable cases of postcraniotomy infection, which can involve compromised skin, an open frontal air sinus, and residual epidural dead space, have been reported. In such cases, reconstructing the scalp and skull is challenging.Methods:Between 2009 and 2016, the author treated 12 patients with recalcitrant postcraniotomy surgical site infections with latissimus dorsi (LD) free flaps. The patients’ ages ranged from 37 to 79 years (mean, 63.5 years), and their underlying diseases included subara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Some authors have reported that the interval should be approximately 3 to 12 months. 14,27 In our cases, six patients received secondary cranioplasty. Yoshioka performed cranioplasty within 3 months of debridement.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Some authors have reported that the interval should be approximately 3 to 12 months. 14,27 In our cases, six patients received secondary cranioplasty. Yoshioka performed cranioplasty within 3 months of debridement.…”
Section: Discussionmentioning
confidence: 92%
“…Some authors have reported successful scalp reconstruction using free flap transfer. [14][15][16][17] Free flap transfer is useful for patients with large scalp and soft tissue defects. To perform secondary cranioplasty safely, the cause of infection should be preoperatively eliminated.…”
mentioning
confidence: 99%
“…The LD free flap combined with a STSG has the disadvantage of changing patient position during flap harvesting. 25 However, we were able to avoid patient reposition during harvest of the serratus anterior flap due to the use of lateral decubitus positioning and contralateral Mayfield pins in the cranium.…”
Section: Discussionmentioning
confidence: 99%
“…Some complications involve partial necrosis and occasional failure of the entire free flap (4%) (Khoury et al, ), while the rate is 6% when head and neck reconstruction are included (Van Driel et al, ). When free flap is needed for large scalp and calvaria reconstruction complications rate is higher (Afifi et al, ; Hierner, van Loon, Goffin, & van Calenbergh, ; O'Connell, Teng, Mendez, & Futran, ; Scaglioni & Giunta, ; Wang et al, ; Yoshioka, ).…”
Section: Discussionmentioning
confidence: 99%